Good Governance in Cooperatives of Nepal-Relationship between Participation and Performance of Cooperatives - Puri, Drona Lal; Sujarittanonta, Lavanchawee (Journal of Education and Vocational Research, 2016)
In this paper, an attempt has been made to examine the relationship between members’ participation and performance of cooperatives of Nepal. The purpose of this paper is to analyze the good governance in cooperatives of Nepal, in the light of the participation and its impact on performance of cooperatives in terms of deposit, volume of transactions, share capital, employment generation, loan investment, consultancy service, amount of reserve fund etc. Members’ participation is selected as independent variable whereas performance of cooperatives is considered as dependent variable in the study. Data are collected from the secondary source from the department of cooperatives of Nepal, Ministry of cooperative and poverty alleviation. Study of 16 types of cooperatives consisting of 5 years of observations from the fiscal year 2010 to 2015 AD has been included in the study. A number of tables, bar diagrams, lines and charts have been used to clarify the data. After all, the study reveals that there is positive relationship there is positive relationship between participation and performance of cooperatives. The study also concludes that good governance in cooperatives is the single most important panacea to achieve the vision, mission, objectives and goals of the cooperatives assuring happiness, rights and liberty of their members through economic, social, cultural and technological changes in their practical lives.